Problematika Implementasi Penilaian Autentik Kurikulum 2013 dalam Pembelajaran Pendidikan Agama Islam Di SD Negeri Ploso I Pacitan - Efi Tri Astuti (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2017)
The main component to know the effectiveness of the learning process is through assessment. The relevance of assessment methods with the curriculum applied in educational institutions is very important. The assessment method relevant with the 2013 curriculum is an authentic assessment. This authentic assessment method measures the competence of attitudes, skills and knowledge based on process and outcome (competence of cognitive, affective, psychomotor). In contrast to the previous curriculum assessment methods that always emphasize cognitive competence (knowledge) and tend to be oriented to exam results, in authentic assessment teachers always pay attention to the balance between attitude competency assessment, knowledge and skills tailored to the development of characteristics of learners in accordance with the ladder. As has been observed in SDN Ploso I Pacitan with the results of the implementation level of authentic assessment of Islamic Education has not been effective. This is constrained by the teacher's lack of awareness in the assessment process.